The strange and the obditive in paranormal speech in Islamic Maghreb - magoura, soumia; bouagada, abdelkader (Journal of Social Sciences and Humanities, 2020)
Maghribiansofism books are full of stranges and oddities of dignity that go beyond sensual perceptions and reality and rise above the mystic world. The strange worked to promote the paranormal speech and made it a way out for all crises facing the fragile categories and tried to achieve sensual pleasure through its aesthetic and attractive character and challenged all what the denied through his scaring speech it has also drawn a picture of the spiritual man wich made him capable to get through time and space his magical of wonder and strange that to go beyond the human abilities. In this research, we will work on identifying the concept of the wondrousand strange in heritage sources and recent studies and clarifying the relationship between them. We have also mentioned the characteristics of the curious and generous types (symbolic, desirable, intimidating, aesthetic) as well as its functions (compensatory, aesthetic, excitement, suspense, sensual enjoyment .. .) And we see to what extent the religious discourse contributed to the consolidation of the wondrous and the generous and the generous and granted it legitimacy to gain a more popular base and attract the largest number of recipients, To paint a picture of a transcendent imagery of the saint, which may be intimidating or enticing, urging his obedience, or even aesthetic in that wondrous characteristic of his dignity. We will also examine in this study the meanings of the symbols that appeared in the karmic discourse and try to break them down to understand how they contributed to the consolidation of these imagined images